The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.11114/jets.v6i10.3663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rapid Weight Loss Practices of Taekwando Athletes and Their Effects

Abstract: This study was conducted to determine the physiological and psychological effects of the weight loss by determining the weight loss methods commonly used by taekwondo athletes. Of the questionnaires evaluated, 107 belonged to female taekwondo athletes and 195 belonged to male taekwondo athletes. The arithmetic average, standard deviation and percent frequency (%) distributions of the obtained data were calculated. It was determined that the; first weight loss age for the competition is 15,66±3,84(kg) in males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Marttinen et al (2011) also mentions an increase in confusion on wrestlers. On the contrary, Seyhan (2018) mentions that there is no positive or negative effect in the mood state of vigor, anger, tiredness or stress detected through an ad hoc questionnaire. In our study, tkd athletes' reports more mood state of fatigue, vigor and anger, but confusion was more reported by wrestlers.…”
Section: Discussionmentioning
confidence: 99%
“…Marttinen et al (2011) also mentions an increase in confusion on wrestlers. On the contrary, Seyhan (2018) mentions that there is no positive or negative effect in the mood state of vigor, anger, tiredness or stress detected through an ad hoc questionnaire. In our study, tkd athletes' reports more mood state of fatigue, vigor and anger, but confusion was more reported by wrestlers.…”
Section: Discussionmentioning
confidence: 99%
“…Dans ce groupe, huit athlètes ont en outre perdu près de 10% de leur poids. Le pourcentage de poids perdu est supérieur à la perte maximale de 4,5% récemment observée au Taekwondo sur une période trois à quatre semaines (Seyhan, 2018). Dans les sports de percussion, comme le Taekwondo, l'amplitude de la perte rapide volontaire de poids semble généralement plus faible que celle des sports de préhension.…”
Section: Resultatsunclassified
“…Seyhan, [17], was found that 26.7% of male judoists lose weight in the last week, and 29.2% of them in the last two weeks; while 27.1% of female judoists lose weight in the last week, and 41.1% of them in the last two weeks. In the study by Xiong et al [14], it was determined as 11.9 days.…”
Section: Discussionmentioning
confidence: 99%
“…This study and the above studies show that the average age of first weight loss for weight category sports athletes is between 12 and 14. It is known that in this ages, in which growth and development are at their highest levels (adolescence period), wrong ways and methods used to lose weight may affect the development of the body, by causing changes in the mechanisms of the endocrine system (testosterone release or insulin-like growth factor-IGF-1) [17]. Therefore, weight loss should be prevented at this age and especially the coaches should be informed about this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation